2018
DOI: 10.1111/hsc.12578
|View full text |Cite
|
Sign up to set email alerts
|

Subgroups of Dutch homeless young adults based on risk- and protective factors for quality of life: Results of a latent class analysis

Abstract: It is important to gain more insight into specific subgroups of homeless young adults (HYA) to enable the development of tailored interventions that adequately meet their diverse needs and to improve their quality of life. Within a heterogeneous sample of HYA, we investigated whether subgroups are distinguishable based on risk- and protective factors for quality of life. In addition, differences between subgroups were examined regarding the socio-demographic characteristics, the use of cognitive coping strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
(129 reference statements)
1
7
0
Order By: Relevance
“…It also found that higher levels of goal-related self-efficacy were positively associated with higher quality of life values [ 55 ]. Another study conducted with youth who experience homelessness used latent class analysis, found that a greater level of resilience acts as a protective factor which is associated with improved quality of life [ 29 ]. The existing evidence and findings from the present study support the positive and instrumental role of resilience in achieving greater quality of life levels among people with experiences of homelessness and mental illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also found that higher levels of goal-related self-efficacy were positively associated with higher quality of life values [ 55 ]. Another study conducted with youth who experience homelessness used latent class analysis, found that a greater level of resilience acts as a protective factor which is associated with improved quality of life [ 29 ]. The existing evidence and findings from the present study support the positive and instrumental role of resilience in achieving greater quality of life levels among people with experiences of homelessness and mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effects of resilience on well-being outcomes in homeless populations are often assessed using cross-sectional [ 23 , 25 ] or qualitative methodological designs [ 26 , 27 ]. To date, a handful of studies have explored this relationship over a short-term longitudinal period (e.g., ≤ 2 years)[ 24 , 29 ]. The Toronto site of the At Home/Chez Soi (AH/CS) Housing First (HF) randomised trial collected six years of longitudinal data on quality of life and resilience measures among individuals with mental illness who were experiencing homelessness at the time of recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…LCA allows for modelling latent‐variable solutions from a set of observable characteristics. LCA has been successfully applied in numerous contexts (Altena, Beijersbergen, Vermunt, & Wolf, 2018; Essau & de la Torre‐Luque, 2019; Forrester, Leoutsakos, Gallo, Thorpe, & Seeman, 2019). Our latent categorical variable was defined as the functioning profile, whose categories were formed by means of the common responses of participants to the profile factors at baseline (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Typological research may reveal similar characteristics among subgroups of homeless individuals, facilitating the implementation of housing and other services that address their specific needs. Some studies have attempted to classify homeless individuals within a broad population [ 2 , 11 ] or in subpopulations such as veterans [ 12 , 13 ] and youth [ 14 , 15 , 16 ]. Several typologies have been established based on previous life experience [ 17 , 18 ], physical or mental health problems [ 13 , 19 , 20 ], quality of life [ 21 , 22 ] and patterns of emergency shelter use [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cluster analyses with homeless individuals have been conducted using multiple variables: sociodemographic (e.g., age and sex), clinical (e.g., mental health disorders (MHD) and substance use disorders (SUD)) and service use (e.g., frequency of emergency department visits (ED) and hospitalizations) [ 2 , 17 , 20 , 25 ]. Some typologies have included risk factors (e.g., victimization and arrest history) and protective factors (e.g., social support and positive perceived health) as pertinent variables [ 15 , 22 ]. However, several variables have been less studied with respect to housing stability, including suicidal behavior and functional disability, both very prevalent in homelessness [ 26 ]; use of public primary care services, such as having a family doctor [ 27 , 28 ]; or required codes of living/conduct in different housing models [ 29 , 30 ], for example enforcing stringent abstinence policies against substance use as opposed to the harm reduction policies characteristic of Housing First, a PH model with case management [ 31 , 32 ], which offers direct access for homeless individuals with serious MHD and/or SUD to a PH without the obligation to participate in treatment [ 33 ].…”
Section: Introductionmentioning
confidence: 99%